2014
DOI: 10.1111/ijd.12426
|View full text |Cite
|
Sign up to set email alerts
|

Insulin resistance in patients with post‐adolescent acne

Abstract: This study suggests that insulin resistance may not play a major role in the pathogenesis of post-adolescent acne. Hormonal changes, genetic susceptibility, stress, the use of cosmetics, drugs, and environmental factors should be considered in the development of post-adolescent acne.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
51
4
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(70 citation statements)
references
References 25 publications
14
51
4
1
Order By: Relevance
“…7 There was no statistically significant difference between mean HOMA-IR of cases and controls in our study. This is similar to the results of studies by Balta et al 3 However a study by Nagpal et al showed significantly high values of HOMA-IR in cases with acne compared to controls. 10 Since acne is a problem in adolescents, the early recognition of insulin resistance might help in better management of acne patients.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…7 There was no statistically significant difference between mean HOMA-IR of cases and controls in our study. This is similar to the results of studies by Balta et al 3 However a study by Nagpal et al showed significantly high values of HOMA-IR in cases with acne compared to controls. 10 Since acne is a problem in adolescents, the early recognition of insulin resistance might help in better management of acne patients.…”
Section: Discussionsupporting
confidence: 91%
“…Also they did not find any significant correlation between acne severity and insulin levels. 3 Some studies have discussed about the positive correlation between blood glucose and severity of acne. This was attributed to increased blood glucose which in turn stimulates increased insulin secretion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because both the gut-skin axis (Bowe et al, 2014;Bowe and Logan, 2011) and dysregulation of insulin signalling (Nagpal et al, 2016;Balta et al, 2015;Kumari and Thappa, 2013;Del Prete et al, 2012) have been implicated in the pathogenesis of adult acne, we designed the current pilot study to evaluate the effect of supplementation with the probiotic strain LGG on skin expression of genes involved in insulin signalling (IGF1 and FOXO1). Our hypothesis was that normalization of insulin signalling in the skin elicited by the probiotic could lead to improvements in the clinical appearance of acne in adult subjects.…”
Section: Page 3 Of 16mentioning
confidence: 99%
“…Accumulating evidence suggests that alterations in insulin signalling may play a significant role in the pathogenesis of adult acne (Cordain et al, 2002;Nagpal et al, 2016;Balta et al, 2015;Kumari and Thappa, 2013;Del Prete et al, 2012). Insulin and insulin-like growth factor-1 (IGF1) have been shown to exert acne-promoting actions (Melnik and Schmitz, 2009) and raised serum IGF1 levels have been associated with increased risk of postadolescent acne in women (Aizawa and Niimura, 1995).…”
Section: Introductionmentioning
confidence: 99%